A case report of takotsubo cardiomyopathy (Indian Journal of Case Reports, 2020)
Takotsubo cardiomyopathy (TC) is defined as the weakening of the left ventricle. It occurs exclusively in women, and it accounts for 1–2% of all cases of suspected acute myocardial infarction, its true prevalence is unknown due to underdiagnosis. It may present with a similar clinical picture mimicking acute myocardial infarction. We report the case of a 53-year-old woman who came to the emergency department with complaints of recurrent vomiting and decreased oral intake. After sometimes, the patient started complaining of chest pain, for which electrocardiography was done, which showed ST-segment elevation. Coronary angiography was done, which showed normal coronary arteries. Afterward, a stressor precipitant was identified. The patient was diagnosed with TC. TC is a great mimic of acute myocardial infarction due to its close resemblance to myocardial infarction in terms of clinical presentation and clinical course. It should be considered as one of the important differentials in patients presenting with acute chest pain.